Brief Report: Relationship Between Serum Infliximab Concentrations and Risk of Infections in Patients Treated for Spondyloarthritis. Issue 1 (28th November 2016) - Bejan‐Angoulvant, Theodora; Ternant, David; Daoued, Fadela; Medina, Frédéric; Bernard, Louis; Mammou, Saloua; Paintaud, Gilles; Mulleman, Denis
Abstract : Objective: Tumor necrosis factor inhibitors are effective in reducing inflammation in rheumatic diseases but increase the risk of infections. This study was undertaken to investigate the relationship between the trough serum concentration of infliximab (IFX) and the risk of a first infection episode. Methods: We retrospectively included all patients who started IFX treatment for an approved indication in our department. Patients were followed up based on recommended IFX infusion schedules. We studied the relationship between the occurrence of a first infection episode requiring hospitalization, anti‐infection treatment, or IFX infusion deferral, and the last trough IFX concentration and mean of the last 3 trough IFX concentrations measured before the infection episode. Results: Of the 201 patients included in the analysis, 173 had spondyloarthritis (SpA). The SpA patients had a mean ± SD age of 46 ± 12 years and a disease duration of 6.2 ± 6.1 years. During a median follow‐up of 1.1 year, 87 SpA patients had at least 1 infection episode. Using Cox models, we found that the probability of survival without infection was significantly higher in patients with a mean of the last 3 trough IFX concentrations lower than the median (<11.3 mg/liter) than in patients with a mean concentration greater than the median ( P  = 0.048 by log‐rank test). Glucocorticoid use and IFX concentration were significantly associated with the risk of a first infection episode in the multivariable analysis ( P  = 0.004 for both). The risk of infection episode was significantly increased in the highest quartile of the mean of the last 3 trough IFX concentrations (>20.3 mg/liter) (hazard ratio 2.65 [95% confidence interval 1.14–6.14], P  = 0.023). Conclusion: Our findings indicate that a high IFX concentration is correlated with a higher risk of a first infection episode, but these findings need to be replicated in further prospective studies.